Development of Sharia Banking and Its Contributions for the Development of National Banking - Thoriqoh Nashrullah Fitriyah (UIN Sunan Gunung Djati Bandung, 2020)
The development and growth of shari'a banks after more than two decades in Indonesia is very spectacular, so that spurred the level of economic growth, but if it is related to the substance of the objectives of sharia bank establishment is the alleviation of poverty and unemployment, it will even increase. Based on data from research studies examining, the contribution of Islamic banking to the development of national law, namely by the existence of people who behave economically in sharia and business behavior of Muslim entrepreneurs are included in the targets of the Islamic economic movement in Indonesia. Even though it looks rather slow, the non-financial side of this economic activity is also growing.